The complete mitochondrial genome of Pallisentis celatus (Acanthocephala) with phylogenetic analysis of acanthocephalans and rotifers - Pan, Ting Shuang; Nie, Pin (Folia parasitologica, 2013)
Acanthocephalans are a small group of obligate endoparasites. They and rotifers are recently placed in a group called Syndermata. However, phylogenetic relationships within classes of acanthocephalans, and between them and rotifers, have not been well resolved, possibly due to the lack of molecular data suitable for such analysis. In this study, the mitochondrial (mt) genome was sequenced from Pallisentis celatus (Van Cleave, 1928), an acanthocephalan in the class Eoacanthocephala, an intestinal parasite of rice-field eel, Monopterus albus (Zuiew, 1793), in China. The complete mt genome sequence of P. celatus is 13 855 bp long, containing 36 genes including 12 protein-coding genes, 22 transfer RNAs (tRNAs) and 2 ribosomal RNAs (rRNAs) as reported for other acanthocephalan species. All genes are encoded on the same strand and in the same direction. Phylogenetic analysis indicated that acanthocephalans are closely related with a clade containing bdelloids, which then correlates with the clade containing monogononts. The class Eoacanthocephala, containing P. celatus and Paratenuisentis ambiguus (Van Cleave, 1921) was closely related to the Palaeacanthocephala. It is thus indicated that acanthocephalans may be just clustered among groups of rotifers. However, the resolving of phylogenetic relationship among all classes of acanthocephalans and between them and rotifers may require further sampling and more molecular data.
Keywords: Acanthocephala; genom mitochondriální; RNA ribozomální; polymerázová řetězová reakce; Polymerase Chain Reaction; zvířata; Genome, Mitochondrial; Animals; vířníci; RNA, Ribosomal; Rotifera; RNA transferová; fylogeneze; Phylogeny; RNA, Transfer